An Identification of English Grammatical Errors in Recount Text Written by Junior High School Students - Pratiwi, Nova Indriana; Saputri, Maulidarni; Pratiwi, Dwiyani; Rachmawati, Arandha May; Saputra, Rizki Aulia (PAEDAGOGIA, 2025)
Writing in English is often considered one of the most challenging skills for EFL learners because it requires the ability to organize ideas clearly and accurately through the correct use of grammar. Many students still struggle with grammatical accuracy, especially in applying English rules such as verb forms, tenses, and sentence structures, which often lead to errors in their written work. This issue becomes particularly evident in writing recount texts, which require consistent use of past tense and proper sentence construction. Therefore, this study aimed to identify the types of grammatical errors and analyze their causes in recount texts written by eighth-grade students at a public junior high school in Banjarnegara Regency. Using a mixed-methods approach with an exploratory design, data were collected through document analysis of ten student texts and analyzed both quantitatively and qualitatively. Quantitative analysis was used to determine the frequency of each error type, while qualitative analysis was applied to interpret the causes of errors based on Richards' (1974) framework, including interlingual, intralingual, and developmental factors. The findings revealed that the most frequent grammatical errors occurred in the use of past tense verbs, subject–verb agreement, and prepositions. Intralingual factors such as overgeneralization, incomplete rule application, and false concept hypotheses were identified as the main causes of the errors, while a smaller number stemmed from interlingual influence. The study highlights the need for more contextualized and continuous grammar instruction to help students develop better grammatical awareness and accuracy in their writing. These findings provide valuable insights for English teachers in designing effective feedback and grammar-integrated writing activities